Determinants of anemia among adolescents girls in district Banggai, Indonesia - Risma, Risma; Hadju, Veni; Zulkifli, Andi; Hidayanti, Healthy; Russeng, Syamsiar S.; Indarty, Apik; Monoarfa, Yustiyanty; Syakir, Mohammad (International Journal of Public Health Science (IJPHS), 2025)
The problem of anemia among adolescent girl in Indonesia is still very high. Many factors cause anemia in adolescent girl. The aim of this study was to assess the prevalence of anemia and its determinants in Banggai district. The research design was cross-sectional, with a sample of adolescent girls aged 12–18 years (n=326). Hemoglobin concentration was measured using a Hemocue hemoglobinometer. The Chi-square test and linear regression analysis were used for data analysis. The results showed that the prevalence of anemia was 48.8%, of which 44.0% had mild anemia and 48.4% had moderate anemia. From the bivariate analysis, anemia was significantly related to adolescent age, father's education, and eating habits (p<0.05). Multivariate logistic regression shows that the factors that most influence the occurrence of anemia are age OR=1.7 (95% CI OR=0.20-0.05) and eating habits OR=2.2 (95% CI OR=0.29-0.81). It was concluded that the prevalence of anemia was high in adolescent girls. Intervention steps are needed to improve the anemia status of adolescent girls in Banggai district.